2000
DOI: 10.1046/j.1365-2346.2000.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of prophylactic droperidol, ondansetron or both in the prevention of postoperative nausea and vomiting in major gynaecological surgery. A prospective, randomized, double-blind clinical trial

Abstract: We conducted a prospective, randomized, double-blind clinical trial comparing droperidol 1.25 mg intravenously (i.v.) (group 1, n = 30), ondansetron 4 mg i.v. (group 2, n = 30), or both (group 3, n = 30) in the prevention of postoperative nausea and vomiting (PONV) in the first 24 h following major gynaecological procedures under combined general and epidural anaesthesia. PONV was analysed by a linear nausea/vomiting score, incidence of nausea and vomiting, and the need for antiemetic rescue. Our results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Nine RCTs provided safety data comparing 5-HT 3RA combination therapy with comparator monotherapy treatmentarms; 5 compared5-HT 3RA1droperidol with droperidol monotherapy,21,24,29.10,44 and 4 compared 5-HT 3RA1dexamethasone with dexamethasone monotherapy. 21,24,29,30,44 Median incidence rates for 5-HT 3RA/steroid treatment groups were headaches 8% (n = 8 studies), dizziness 4% (6), drowsiness 3% (6), dizziness0% (5), and any adverse event 9% (6). Infrequently reported adverseevents included pulmonary (oxygensaturation [Sa02] <94%),42 cardiac abnormalltiesj!…”
Section: Among-study Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine RCTs provided safety data comparing 5-HT 3RA combination therapy with comparator monotherapy treatmentarms; 5 compared5-HT 3RA1droperidol with droperidol monotherapy,21,24,29.10,44 and 4 compared 5-HT 3RA1dexamethasone with dexamethasone monotherapy. 21,24,29,30,44 Median incidence rates for 5-HT 3RA/steroid treatment groups were headaches 8% (n = 8 studies), dizziness 4% (6), drowsiness 3% (6), dizziness0% (5), and any adverse event 9% (6). Infrequently reported adverseevents included pulmonary (oxygensaturation [Sa02] <94%),42 cardiac abnormalltiesj!…”
Section: Among-study Comparisonsmentioning
confidence: 99%
“…There were no reports of pulmonary complications, extrapyramidal symptoms, avascular necrosis, occult infection, or delayed wound healing among studies using combinations of 5-HT JRAs with droperidol for prophylaxis of PONVJ1, 24,27,29,30,44 Although one study by Eberhart et al," reported cardiac abnormalities, the incidence of arrhythmias in patients treated with dolasetron/droperidol was nearly identical to that observed in patients administered placebo (3.9% vs 3.8%), as was that for bradycardia (23.7% vs 25.6%) and cardiovascular adverse effects, including hypertension or hypotension requiring treatment (9.2% vs 9.0%).…”
Section: Sht 3ra Combination Therapiesmentioning
confidence: 99%
“…immdeiately before induction of anesthesia, was more effective than granisetron or droperidol for preventing PONV [47]. By contrast, Peixoto et al found no difference in the efficacy between patients receiving droperidol 1.25 mg and ondansetron 4 mg and those receiving each drug alone [48].…”
Section: Combinatioin Antiemetic Therapy and Multimodal Management Stmentioning
confidence: 94%
“…Therefore, it is possible that a combination of antiemetics with different sites of activity would be more effective than one drug alone. Combination antiemetic therapy is effective for preventing PONV in women undergoing major gynecological surgery [46][47][48][49][50][51] (Table 4). Three investigations evaluated the efficacy of serotonin receptor antagonists (ondansetron, granisetron) with droperidol in the prevention of PONV [46][47][48][49][50].…”
Section: Combinatioin Antiemetic Therapy and Multimodal Management Stmentioning
confidence: 99%
“…; Peixoto et al . ). There are several factors causing PONV, generally related to the particular surgical procedure or patient‐specific risk factors.…”
Section: Introductionmentioning
confidence: 97%